A Possible Role for CD8+ T Lymphocytes in the Cell-Mediated Pathogenesis of Pemphigus Vulgaris. (18th November 2013) - Giurdanella, Federica; Fania, Luca; Gnarra, Maria; Toto, Paola; Di Rollo, Daniela; Sauder, Daniel N.; Feliciani, Claudio
Abstract : Pemphigus vulgaris (PV) is an autoimmune blistering disease whose pathogenesis involves both humoral and cell-mediated immune response. Though the pathogenetic role of autoantibodies directed against desmoglein 3 is certain, a number of other factors have been suggested to determine acantholysis in PV. In this study we examined the possible role of CD8+ T cells in the development of acantholysis by a passive transfer of PV autoantibodies using CD8 deficient mice, and we also studied the inflammatory infiltrate of PV skin lesions by immunohistochemical staining. The results of the immunohistochemical staining to study the expression of CD3, CD4, and CD8 in PV skin lesions showed that CD4+ are more expressed than CD8+ in the inflammatory infiltrate of PV lesions, confirming the data of the previous literature. The passive transfer study showed a lower incidence of pemphigus in the group of CD8 deficient mice compared to the control one of wild-type mice. These results suggest that CD8+ T cells may play a role in the pathogenesis of PV, perhaps through the Fas/FasL pathway.